Planejamento e controle de produção, um estudo de caso para implementação de um sistema de padronização de processos no setor produtivo de uma indústria marmorista situada na cidade de Nova Araçá - Cervieri, Eduardo Victor (2022)
Production planning and control is something that has been increasingly consolidated in our daily lives, including in small industries. This leads to deep analyzes of the production process in order to constantly improve it, therefore, this article aims to measure the total time and the steps that lead from the beginning to the end of the production process of two items of the standardized line of design furniture in a marble industry, also analyzing the delays found during the manufacture of the items. In the course of this case study, a qualitative approach with a descriptive nature was used with primary data collection in the field. The measurements obtained from the observations led to a broad knowledge of the strengths and weaknesses of the production process, thus, it is possible to diagnose the slowness of each stage. Therefore, the results found were positive in terms of the various possibilities for improvements to be applied by the organization's manager.